Risk factors for the development of macular edema in children with uveitis - Friling, Ronit; Berliner, Ori; Eiger-Moscovich, Maya; Chen, Yi-Hsing; Tomkins-Netzer, Oren; Kramer, Michal (Frontiers in Ophthalmology, 2023)
Aim: To determine the risk factors for macular edema (ME) in children with uveitis. Methods: We retrospectively evaluated 264 eyes of 150 pediatric uveitic patients. Data included demographics, type of uveitis, etiology, clinical findings, treatment, and time to develop ME. Risk factors for the development of ME were studied. Results: Sixty-three eyes (23.86%) developed ME at a mean time of 15.3±2.95 months, at a rate of 0.08 eyes per eye-year. Risk factors for developing ME in univariate analysis were non-anterior uveitis (p=0.002), band keratopathy (p <0.0001); posterior synechiae (p=0.003), cataract (p=0.002), and vision impairment at presentation (p <0.0001). In a multivariate analysis, non-anterior uveitis, and vision impairment remained independent risk factors. Conclusion: ME was most common among pediatric uveitic eyes with non-anterior uveitis followed by those who present with complications, such as band keratopathy and posterior synechia. These findings may indicate close follow-up for early detection of ME.